EDUCATION MANAGEMENT AND ADMINISTRATION - Asri Yuni vikasari; Abd Rahman; Iwan Setiawan; Yuyun Rohmatul (Media Inovasi Pendidikan dan Publikasi, 2023)
In an educational institution, of course, requires the management of the education system in order to achieve the educational goals that have been set. As for what will become a problem in the management of education, namely unclear and ineffective planning, lack of transparency and accountability in education management, the availability of facilities and infrastructure that is less supportive and the absence of developing educational programs that are in accordance with community needs. This type of article writing method is qualitative, while the approach used is library research or library research. The author seeks and collects information about education management and administration from library sources including journal articles and books. The purpose of writing this article is to explain the meaning of Education management and Education administration, the functions of Education management and administration and the field of Education management and administration.